2021
DOI: 10.3389/fncir.2021.655502
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Intermittent Theta-Burst Stimulation Reduces Upper Limb Spasticity After Subacute Stroke: A Randomized Controlled Trial

Abstract: Objective: This study aims to explore the efficacy of cerebellar intermittent theta-burst stimulation (iTBS) on upper limb spasticity in subacute stroke patients.Methods: A total of 32 patients with upper limb spasticity were enrolled and randomly assigned to treatment with cerebellar iTBS or sham stimulation before conventional physical therapy daily for 2 weeks. The primary outcomes included the modified Ashworth scale (MAS), the modified Tardieu scale (MTS), and the shear wave velocity (SWV). The secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…Random sequence generation or allocation concealment scored a high risk of bias or unclear risk in four of the included studies, which led to the error of the result to increase ( 15 , 21 , 23 , 25 ). Blinding of participants and personnel scored unclear risk in some of the included studies, which was inherent to the intervention ( 15 , 17 , 18 , 23 , 26 – 28 , 30 – 32 ). According to certain studies, the blinding of outcome assessment was not specified adequately, resulting in a score that was unclear or high in the detection bias ( 22 , 23 , 25 , 28 , 30 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Random sequence generation or allocation concealment scored a high risk of bias or unclear risk in four of the included studies, which led to the error of the result to increase ( 15 , 21 , 23 , 25 ). Blinding of participants and personnel scored unclear risk in some of the included studies, which was inherent to the intervention ( 15 , 17 , 18 , 23 , 26 – 28 , 30 – 32 ). According to certain studies, the blinding of outcome assessment was not specified adequately, resulting in a score that was unclear or high in the detection bias ( 22 , 23 , 25 , 28 , 30 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…More research is required in the future to corroborate this conclusion. According to the included studies, it was widely believed that iTBS delivered a 2-s train of bursts consisting of three 50-Hz pulses repeated every 200 ms (5 Hz) at an intensity of 70–80% AMT or RMT every 10 s for 20 times (600 pulses total), which was the most beneficial plan ( 15 , 16 , 18 , 21 , 23 , 26 , 27 , 30 ). At the same time, the majority of studies had positive benefits after 2 weeks or 10 sessions, which warrants further investigation ( 15 , 17 19 , 21 – 28 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant decrease in the modified Ashworth scale (MAS), the modified Tardieu scale (MTS), and upper limb elastography values were noted in the iTBS group compared to sham, leading to the conclusion that ipsilesional cerebellar iTBS can reinforce physical therapy gains in upper limp poststroke spasticity. The possible mechanisms include, according to the authors, the induced plasticity in Purkinje-cell level, as well as the influence on spinal neurons responsible for muscle tone adjustments [ 44 ]. Clinical studies concerning cerebellar TMS applications in stroke rehabilitation are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In patients after stroke, the balance between the two hemispheres of the brain is disrupted, resulting in hyperexcitability of the unaffected hemisphere and increased inhibition of the affected hemisphere [ 46 ]. Most of the reported findings showed that LF-rTMS had a positive effect on post-stroke spasticity [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%